K-12 Engineering and the Next Generation Science Standards (NGSS): A Network Visualization and Analysis - Reitsma,Reindert; Hoglund,Brian; Marks,Andrea; Chaker,Dua; Marks,Andrea (American Society for Engineering Education (ASEE), 2020)
We present an interactive network visualization of the Next Generation Science Standards (NGSS) and its coverage by collections of aligned curriculum. The visualization presents an alternative to the usual presentation of the NGSS as a set of linked tables. Users can view entire grade bands, search for or drill down to the level of individual NGSS standards or curricular items, or display groups of standards across grade bands. NGSS-aligned curriculum collections can be switched on and off to visually explore their NGSS coverage. Viewing the NGSS and associated curriculum this way facilitates navigating the NGSS and can help with assessment of alignments as lacking or anomalous. Modeling the NGSS as a network also allows for the computation of network metrics to provide insight into core characteristics of the network. It also provides for detecting anomalies and unexpected patterns.
Keywords: BIS; Design Program